Desafíos contemporáneos para el socialismo en Cuba (A propósito de las reformas políticoeconómicas en la fase actual de la revolución) - Güendel, Hermann (2010)
This essay analyzes on the origin and impact of the amendment process currently undertaken by the Cuban government authorities considering it as the result of --what I call-- super structural imbalance. Such imbalance is caused by the application of the System for Management and Planning of the Economy. To our judgment, the process of amendment both structurally and super structurally conforms the new phase in the construction of the Socialism in the island from a coherent point of view to what it has been until now as a political constant of the revolution: the vindication of the human being as the promoter of its historical reality.